El uso de las plataformas digitales y sus prácticas en las ventas del “Depósito Jenny” en el cantón Guano periodo 2021. - Gusqui Estrada, Jenny Paulina (2023)
The present research aims to determine how the use of digital platforms and their practices affect the sales of "Jenny Warehouse" in the canton Guano period 2021, for which the hypothetical deductive method was used, through the approach of descriptive and field research, non-experimental design. Likewise, it was established as a study population of customers who buy products in the company, based on a sample of 107 people, in which information could be extracted through the survey application, which allowed the respective analysis and interpretation of the data obtained; therefore, the chi-square test was performed in the SPSS program, where the value of sample X was 16.331 which was more significant than the value X2 9, thus rejecting the null hypothesis and accepting the alternative indicating that the use of digital platforms affects the sales practices of the "Jenny Deposit" in the Guano canton period 2021. In conclusion, the company Jenny warehouse has a deficit in its sales because it does not adequately promote its products, misuses the digital platform with which the company without taking advantage of its strengths and benefits to improve its sales, besides that, it was handled in a practical way which has generated little affluence and loss of customers in the store, for this reason, it has been seen the importance of selecting a digital platform which must be used correctly and constantly by the owner of the company.